Biohydrogel induced soil–water interactions: how to untangle the gel effect? A review. Issue 2 (23rd January 2017) - Brax, Mathilde; Buchmann, Christian; Schaumann, Gabriele Ellen
Abstract: Biohydrogels such as microbial exudates and root‐derived mucilage are soil‐born cross‐linked polymers, able to form porous three‐dimensional networks during water uptake. The gel effect is the variation of soil properties, such as soil hydrology and soil structural stability, resulting from biohydrogel swelling in soil. Conventionally, soil–water–hydrogel interactions are investigated by measuring soil bulk properties such as water retention curves and porosity, without further analyzing the effect of biohydrogel phases in soil on a quantitative basis. Therefore, the evaluation of advanced and novel methods for the characterization of biohydrogel phases in soil and soil–water–hydrogel interactions is necessary. This review evaluates currently available methods for their potential to analyze processes associated to the gel effect. A promising approach to investigate the spatio‐temporal distribution of biohydrogel phases in porous media is based on Nuclear Magnetic Resonance (NMR) such as 1 H‐NMR relaxometry, as well as on imaging techniques such as Environmental Scanning Electron Microscopy (ESEM). Especially NMR techniques enable the identification of different water populations based on their differences in the relaxation, and thus the mobility of water molecules in biohydrogels and non‐gel water in soil pores. Rheology measures the flow behavior of biohydrogels, providing information on the structural behavior of the hydrogel network and its gelling mechanism. Soil rheology further quantifies the effect of the biohydrogel phases on the interactions between soil particles, and thus the impact on soil microstructural stability. However, rheology does not elucidate the spatio‐temporal distribution and structural state of biohydrogel phases in soil. All in all, a systematic combination of rheology, NMR and suitable imaging methods seems promising and necessary in order to elucidate the still widely unknown gel effect in soil.